Wnt Glycation Inhibits Canonical Signaling - Ye, Zhennan (Cells, 2019)
Glycation occurs as a non-enzymatic reaction between amino and thiol groups of proteins, lipids, and nucleotides with reducing sugars or α-dicarbonyl metabolites. The chemical reaction underlying is the Maillard reaction leading to the formation of a heterogeneous group of compounds named advanced glycation end products (AGEs). Deleterious effects have been observed to accompany glycation such as alterations of protein structure and function resulting in crosslinking and accumulation of insoluble protein aggregates. A substantial body of evidence associates glycation with aging. Wnt signaling plays a fundamental role in stem cell biology as well as in regeneration and repair mechanisms. Emerging evidence implicates that changes in Wnt/β-catenin pathway activity contribute to the aging process. Here, we investigated the effect of glycation of Wnt3a on its signaling activity. Methods: Glycation was induced by treatment of Wnt3a-conditioned medium (CM) with glyoxal (GO). Effects on Wnt3a signaling activity were analyzed by Topflash/Fopflash reporter gene assay, co-immunoprecipitation, and quantitative RT-PCR. Results: Our data show that GO-treatment results in glycation of Wnt3a. Glycated Wnt3a suppresses β-catenin transcriptional activity in reporter gene assays, reduced binding of β-catenin to T-cell factor 4 (TCF-4) and extenuated transcription of Wnt/β-catenin target genes. Conclusions: GO-induced glycation impairs Wnt3a signaling function.